The Christmas star : a novel - VanLiere, Donna, 1966- (St. Martin's Press, 2018)
Thirty-two-year-old Amy Denison volunteers at Glory<U+2019>s Place, an after school program where she meets seven-year-old Maddie, a precocious young girl who has spent her childhood in foster care. Unbeknownst to Amy, Maddie is a mini-matchmaker, with her eye on just the right man for Amy at Grandon Elementary School, where she is a student. Amy is hesitant <U+2013> she<U+2019>s been hurt before, and isn<U+2019>t sure she<U+2019>s ready to lose her heart again <U+2013> but an unexpected surprise makes her reconsider her lonely lifestyle. As Christmas nears and the town is blanketed in snow and beautiful decorations, Maddie and the charming staff at Glory<U+2019>s Place help Amy to see that romance can be more than heartache and broken promises.